Critical Review on Kashtartava (Dysmenorrhea-Menstrual Pain) and its Ayurvedic Management - nain, Om Prakash; kumar, Praveen (International Research Journal of Ayurveda & Yoga, 2023)
Dysmenorrhea is currently society’s top health concern because of today’s sedentary lifestyle and lack of exercise. Women today must deal with obstacles brought on by hectic lives that lead to Mithyaahara and Vihara, overexertion and malnutrition, which can result in Vikruti in "Rituchakra" and a variety of Vyadhis related to menstruation. To effectively treat dysmenorrhoea, Ayurveda suggests Ritucharya and Dinacharya, food modification, and frequent practise of yoga in the form of asanas, pranayam, and meditation. Likewise, if necessary, Uttarbasti, Garbhashaya Balya Aushadhi, Anuvasana, or Matrabasti can also be used. Stress is becoming a necessary component of modern life. A woman’s health has been deteriorating as a result of her never ending search for material comforts. The primary cause of women’s various issues is that they have not been adhering to the rules of healthy life. She has ignored the rules for maintaining a healthy body and mind. Menstruation is a natural occurrence that occurs as part of a woman’s regular reproductive cycle. According to Ayurveda texts, Kashtartava is regarded as and characterised as a symptom of numerous different ailments. As a result, this study focuses on review of Kashtartava and its treatment as in classical references.